Fostering Loyalty and Creativity: How Organizational Culture Shapes Employee Commitment and Innovation in South Korean Firms - Jiangmin Ding; Gahye Hong (Behavioral Sciences)
Organizational culture, human capital, and innovative capabilities are essential resources for any business, particularly during challenging times. Companies can leverage these resources to gain a competitive advantage. Based on social exchange theory, this study explores the impact of corporate culture on employee commitment and innovative behavior at the individual level, emphasizing the importance of innovation within employee roles. Using 9512 valid data points from the Human Capital Corporate Panel (HCCP), this study validates the research model and hypotheses. The results indicate that an innovation-oriented organizational culture significantly enhances employees’ organizational commitment, which in turn promotes innovative behavior. Organizational commitment is a positive mediating factor in this process. Furthermore, a relationship-oriented culture positively moderates the influence of innovation culture on employees’ organizational commitment. Situated in the Korean context, where Confucian values and collectivism strongly influence workplace dynamics, this study highlights the importance of aligning innovation efforts with cultural expectations. The results suggest that fostering innovative and relational cultural values can be a powerful method in encouraging commitment and creativity, especially in the Korean context companies.